Analisis Pengukuran Produktivitas Kerja Karyawan Pada Proses Fabrikasi di Machining Bay dengan Metode Stopwatch Time Study di PT. XYZ - Auliya Aisyah Putri; Abdul Alimul Karim (Journal of Industrial Innovation and Safety Engineering (JINSENG), 2024)
PT. XYZ is a company that engaged in the heavy equipment repair industry. In carrying out the company's business processes, the departments at PT. XYZ is required to be integrated with each other in order to achieve productivity. One of the departments at PT. XYZ is a fabrication department, which consists of a welding bay and a machining bay. This department consists of 3 workers with 1 main operator and 2 helpers. The level of productivity in this department is still below 80% or at a low level. In calculating worker productivity, data was collected using the stopwatch time study method. Furthermore, the data is classified as productive, supporting, and also non-productive activities according to the company's criteria. Then a Pareto Chart is formed to determine the largest percentage of causes from non-productive activities and also supports it along with a fishbone diagram that shows the root cause of the problems in the machining bay department. In the machining bay fabrication process, employee productivity only reaches 42% and support at 30%, and the non-productive rate reaches 28%. Pareto analysis was carried out in the support and non-productive categories, obtained a cumulative percentage of 80% in the support category, namely weekly routine at 33%, discussion at 31%, and clean up at 26%, while in the non-productive category there was rest with 41%, waiting at 24%, and personal time by 22%. Based on the Pareto chart that has been analyzed, the problems that dominate in the machining bay are re-analyzed regarding the root problems that occur at PT. XYZ. Based on the fishbone diagram, the main problems occur in man, method, management, and machine.